(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the reasons that prevent male adherence to Men’s Health Care Programs. To this end, a qualitative study was carried out, carried out in a Teaching Hospital with 30 men who sought the Adult Emergency Service, received and answered a semi-structured questionnaire in August 2018, the data obtained were transcribed to a electronic bank and received statistical analysis and data description. In view of the analysis, it was possible to discuss that the reason for the impediment was work, and the most frequent suggestions were to open on weekends; appointments after business hours; and more doctors for care. Given the above, it was possible to conclude that it is necessary to adopt strategies to encourage the male population to seek primary health care services through the media and the active search by health agents in Basic Health Units, actions and guidelines can contribute to improving the adhesion of the male population to the programs of the National Policy for Integral Attention to Men’s Health.